Challenges on tuberculosis care in health care facilities during COVID-19 pandemic: Indonesian perspective - Wira Winardi; Hendra Wahyuni; Moulid Hidayat; Aditya Wirawan; Fariz Nurwidya; Mohammad N. Uddin; Mohamad Yusup (Narra Sains Indonesia, 2022)
Indonesia is among the top three countries globally with the highest tuberculosis burden. During the past decades, Indonesian health authorities have struggled to improve tuberculosis care quality in health care facilities by optimizing the regulation and strengthening the private sector contributions. The coronavirus disease 2019 (COVID-19) pandemic has hardly affected the Indonesian health care system, including the National Tuberculosis Control Program. While the end of the COVID-19 pandemic in Indonesia is uncertain, the measure to control tuberculosis must not be weakened. Early identification and measurement of the problem size are essential to decide the most appropriate approach to maintain the sustainability of National Tuberculosis Control Program, particularly in health care facilities during the COVID-19 pandemic. This article points out the possible threats to the sustainability of TB care in Indonesia during the COVID-19 pandemic, including some approaches to overcome those problems.